2009
DOI: 10.5194/acp-9-7531-2009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ship-plume chemistry using a newly-developed photochemical/dynamic ship-plume model

Abstract: Abstract.A photochemical/dynamic ship-plume model, which can consider the ship-plume dynamics and ship-plume chemistry, simultaneously, was developed to gain a better understanding of atmospheric impact of ship emissions. The model performance was then evaluated by a comparison with the observation data measured on a NOAA WP-3D flight during the Intercontinental Transport and Chemical Transformation 2002 (ITCT 2K2) airborne field campaign. The simulation conditions and parameters, such as meteorological condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(90 citation statements)
references
References 62 publications
3
86
1
Order By: Relevance
“…Schlager et al (2008) 184 a Kim et al (2009) 6.25 b Chen et al (2005) 13.4 Song et al (2003) 4-20 von 19.1 Eyring et al (2005) 9.31 c This study 20 a The emission strengths reported by Franke et al (2008) and Schlager et al (2008) hold for "fairly large container ships". b Based on Chen et al (2005).…”
Section: Sensitivity Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…Schlager et al (2008) 184 a Kim et al (2009) 6.25 b Chen et al (2005) 13.4 Song et al (2003) 4-20 von 19.1 Eyring et al (2005) 9.31 c This study 20 a The emission strengths reported by Franke et al (2008) and Schlager et al (2008) hold for "fairly large container ships". b Based on Chen et al (2005).…”
Section: Sensitivity Analysismentioning
confidence: 89%
“…the measurements the wind speed was between 9 and 11 m s −1 , in this comparison we set the wind speed to 10 m s −1 . The height of the marine boundary layer determined from aircraft measurements was 350 m. The ambient temperature was 290 K. We set the stability class to "moderately stable", following a recent study by Kim et al (2009). Figure 1 shows the evolution of observed and simulated NO x , O 3 and OH concentrations, as well as the instantaneous NO x lifetime, in the plume during the 3 h after emissions.…”
Section: Evaluation Of Paranoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, many detailed analyses of the impacts of ocean-going ship emissions on atmospheric MBL chemistry and the global radiation budget have been carried out in a range of aspects: (1) O 3 /HO x /NO y photochemistry in the MBL (e.g., Lawrence and Crutzen, 1999;Endresen et al, 2003;Song et al, 2003a;von Glasow et al, 2003;Kim et al, 2009); (2) sulfur cycle in the MBL (e.g., Capaldo et al, 1999;Song et al, 2003b;Faloona, 2009); and (3) impacts on the global radiation budget (e.g., Capaldo et al, 1999;Endresen et al, 2003;Langley et al, 2010).…”
mentioning
confidence: 99%
“…A ship-plume photochemical/dynamic model developed previously by Kim et al (2009) was used to help answer these scientific questions. In addition, in terms of the ship-plume photochemical/dynamic model development and its applications, this is a companion study of Kim et al (2009) with a particular focus on ship-plume HCHO. This study first discusses a ship-plume case from the Intercontinental Transport and Chemical Transformation 2002 (ITCT 2K2) campaign as a base study case (hereafter, called "ITCT 2K2 ship-plume case").…”
mentioning
confidence: 99%